Terrestrial-To-Satellite Interference In The C band: Tractable Calculation Technique - A., Hameed; Abdulrazak, Lway Faisal (JATIT & LLS, 2014)
This paper presents a research conducted on the interference mitigation between IMT-Advanced and Fixed Satellite Services (FSS). It covers a deterministic analysis for interference to noise ratio (I/N), adjacent channel interference ratio (ACIR) and path loss propagation, in order to determine the separation distances in the co-channel interference (CCI) and adjacent channel Interference (ACI) scenarios. An analytical model has been developed based on the deterministic analysis of the pr opagation model. The IMT-Advanced parameters have been represented by Worldwide Interoperability for Microwave Access (WiMAX) 802.16e. The impact of different FSS channel bandwidths, guard band separations, antenna heights and different deployment areas on co-existence feas ibility are considered. The results obtained in terms of minimum required separation distance in three scenarios, co-channel, zero-guard band, and adjacent channel are analyzed.